(untitled) (Indian Journal of Arid Horticulture, 2025)
Mostly cucurbitaceous vegetables are grown in the main season, which is always less profitable, because of markets are flooded with lot of vegetables at that time. The prices of same vegetables are higher during the off- season. It is difficult to grow cucurbits in winter season because of low temperature and frost injury and thereby adverse effect on growth and fruit setting. Polythene low tunnel technology for production of summer squash, musk melon and water melon is very common in Israel (Singh et al. 2001). This technology is suitable for northern plains where the might temperature during winter season (De- cember-January) goes below 5°C (Singh and Sirohi, 2006). The high temperature inside low tunnels make the crop period short, when it is needed to expedite the crop growth and protect the plants from natural disasters like hails in- jury, cold winds and advance the crop by 45-60 days then their normal season. This low-cost technology for off-sea- son cultivation of cucurbits is very simple and highly prof- itable for vegetable growers. For the development and evaluation of the technology a field experiment was con- ducted at farmer’s field in the command area of Chhitoli irrigation project under RWSRP to find out the suitable sowing time of summer squash under polythene low tun- nels for off-season cultivation.